Daniel McAlpine and The Bitter Pit - Parbery, Douglas G. (Springer International Publishing : Imprint: Springer, 2015)
Part I consists of 6 chapters. The first three cover McAlpine's early education, work and influences which drew him into science. How Thomas Huxley and William Thislton-Dyer ignited his interest in biology and follows his achievements in Edinburgh including his remarkable teaching atlases and his remarkable ability a lecturer/educator, admired by his students in Edinburgh and Melbourne. Three more chapters review his impact on tertiary education in Australia, and his establishment as a renowned scientist in Australia. It explores his expertise in mycology and plant pathology and reasons for his rise to international prominence in the context of developments in Europe and Australia. Chapter 6 is a review of his 20 years as a plant pathologist, as he wrote it. Part II is based on previously unpublished documents that deal with an investigation of the cause and control of a devastating disease of apples, bitter pit. McAlpine was reluctantly drawn into leading it, largely unaware that the Government Botanist, Professor A.J. Ewart, was jealous of him and wanted to lead the investigation himself. Ewart weakened the faith of McAlpine's political masters in him who claimed he failed in not discovering the cause of bitter pit. We now know, that the vital information needed to understand the cause remained unknown to science until almost 25 years after McAlpine's death and the understanding of the cause took another 20 or more years. He retired under an ignominious cloud of ingratitude, deeply hurt and angered. Part III examines the impact of his loss of employment on him and the lost of potential benefit to plant pathology. The final chapter follows how a daughter worked for half a century with those who had first hand experience of McAlpine's ability, rigour and reliability in restoring his reputation to its rightful place.